Relationship of Knowledge and Motivation with Compliance in Taking Anti-Tuberculosis Drugs in TB Patients at North Bontang Health Center 1 - husna, Husna husna; Leswana, Nurillahi Febria; Butar-Butar, Maria Elvina Tresia (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Tuberculosis (TB) treatment requires six months of continuous Anti-Tuberculosis Drug (OAT) therapy; non-compliance leads to treatment failure and Multi-Drug Resistant TB. This study aimed to analyze the relationship between patient knowledge and motivation with medication compliance among TB patients at the North Bontang Health Center 1, Indonesia. This cross-sectional study involved tuberculosis patients at North Bontang 1 Health Center. From a total registered population of 325 patients, a strict purposive sampling technique was applied based on inclusion and exclusion criteria, resulting in 30 eligible patients who participated in this study during the period of December 2024 to January 2025. Data on knowledge and motivation were collected using structured questionnaires; compliance was determined via triangulation (interviews, TB Form 01, PMO). Bivariate analysis used the Fisher's Exact Test (n=30). Results showed the majority demonstrated good knowledge (83.3%) and high motivation (90.0%), resulting in a high overall compliance rate (93.3%). Statistical analysis revealed a significant relationship between knowledge and compliance (p=0.006). No statistically significant relationship was found between motivation and compliance (p=0.193), likely due to data homogeneity